Design of a laboratory hydraulic device for testing of hydraulic pumps - Pavel Máchal (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2013)
The present contribution deals with solves problem of research of testing device to monitor of hydrostatic pumps durability about dynamic loading under laboratory conditions. When carrying out the design of testing device are based on load characteristics of tractor hydraulic circuit, the individual characteristics of hydraulic components and performed calculations. Load characteristics on the tractors CASE IH Magnum 310, JOHN DEERE 8100, ZETOR FORTERRA 114 41 and Fendt 926 Vario were measured. Design of a hydraulic laboratory device is based on the need for testing new types of hydraulic pumps or various types of hydraulic fluids. When creating of hydraulic device we focused on testing hydraulic pumps used in agricultural and forestry tractors. Proportional pressure control valve is an active member of the hydraulic device, which provides change of a continuous control signal into relative pressure of operating fluid. The advantage of a designed hydraulic system is possibility of simulation of dynamic operating loading, which is obtained by measurement under real conditions, and thereby creates laboratory conditions as close to real conditions as possible. The laboratory device is constructed at the Department of Transport and Handling, Faculty of Engineering, Slovak University of Agriculture in Nitra.